Increasing the Solubility Limit for Tetrahedral Aluminium in ZnO:Al Nanorods by Variation in Synthesis Parameters. (12th July 2015) - Kelchtermans, Anke; Adriaensens, Peter; Slocombe, Daniel; Kuznetsov, Vladimir L.; Hadermann, Joke; Riskin, Alexander; Elen, Ken; Edwards, Peter P.; Hardy, An; Van Bael, Marlies K.
Abstract : Nanocrystalline ZnO:Al nanoparticles are suitable building blocks for transparent conductive layers. As the concentration of substitutional tetrahedral Al is an important factor for improving conductivity, here we aim to increase the fraction of substitutional Al. To this end, synthesis parameters of a solvothermal reaction yielding ZnO:Al nanorods were varied. A unique set of complementary techniques was combined to reveal the exact position of the aluminium ions in the ZnO lattice and demonstrated its importance in order to evaluate the potential of ZnO:Al nanocrystals as optimal building blocks for solution deposited transparent conductive oxide layers. Both an extension of the solvothermal reaction time and stirring during solvothermal treatment result in a higher total tetrahedral aluminium content in the ZnO lattice. However, only the longer solvothermal treatment effectively results in an increase of the substitutional positions aimed for.